Accumulating Evidence for Dance/Movement Therapy in Cancer Care - Goodill, Sharon W. (Frontiers in Psychology, 2018)
This review offers a discussion of the state of dance/movement therapy research with people living with cancer. The vast majority of extant studies published in the English language are with women with breast cancer. An examination of challenges facing dance/movement therapy researchers in this area is provided, and recommendations for research foci and priorities are outlined. These include qualitative syntheses, integration of implementation evidence with qualitative synthesis, and formal process evaluation studies.